Method for manufacturing lithium secondary battery
By adjusting the electrolyte injection amount and pre-charge/pre-discharge times during the manufacturing process of the lithium secondary battery, increasing the friction between the battery case and the electrode assembly, the separation and leakage problems of the soft-pack lithium secondary battery under external impact are solved, and its impact resistance is significantly improved.
Patent Information
- Application Number
- CN202380055730.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-21
- Publication Date
- 2025-03-11
AI Technical Summary
Soft-pack lithium secondary batteries are prone to separation of electrode assembly and leakage of electrolyte under external impact, and lack sufficient impact resistance.
By ensuring that the electrolyte injection amount and pre-charge/pre-discharge times meet a specific relationship when manufacturing the battery, the friction between the battery case and the electrode assembly is increased. Specific methods include preparing a battery case, setting up an electrode assembly, injecting an electrolyte, activating a battery cell, and performing pre-charge/pre-discharge operations to meet a specific friction range.
The friction between the electrode assembly and the battery case is significantly increased, the electrode assembly separation and electrolyte leakage caused by external impact are suppressed, and the impact resistance of the lithium secondary battery is improved.
Smart Images

Figure CN119605017A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for manufacturing a lithium secondary battery, and in particular, to a method for manufacturing a lithium secondary battery with excellent impact resistance. Background Art
[0002] Lithium secondary batteries are generally manufactured in the following manner: electrode active material slurry is applied to positive electrode collectors and negative electrode collectors to prepare positive and negative electrodes, the positive and negative electrodes are stacked on both sides of a separator to form an electrode assembly having a predetermined shape, and then the electrode assembly is housed in a soft package and injected with an electrolyte.
[0003] According to the shell material of the electrode assembly, the secondary battery can be divided into a soft pack type secondary battery and a can type secondary battery. Specifically, the can type secondary battery is manufactured by pressing the flexible soft pack film laminate to form a cup portion, accommodating the electrode assembly in the cup portion, injecting the electrolyte and then sealing the sealing portion to manufacture the soft pack type secondary battery, thereby accommodating the electrode assembly in a can formed of metal, injecting the electrolyte and then assembling the top cover on the upper part of the can and sealing it.
[0004] Soft-pack secondary batteries are lightweight, have excellent space utilization, and are able to achieve high energy density by using a stacked electrode assembly, but are more susceptible to external impact than can-type secondary batteries. Nowadays, since secondary batteries are used in various environments, they are required to provide excellent safety even in harsh environments, so it is necessary to improve the impact resistance of soft-pack secondary batteries. Summary of the invention
[0005] Technical issues
[0006] To solve the above problems, one aspect of the present disclosure provides a method of manufacturing a lithium secondary battery, which increases friction between a battery case and an electrode assembly by ensuring that an electrolyte injection amount and pre-charge / pre-discharge times satisfy a specific relationship when manufacturing the battery.
[0007] Technical Solution
[0008] According to one aspect of the present disclosure, there is provided a method for manufacturing a lithium secondary battery, the method comprising: a first step of preparing a battery case; a second step of disposing an electrode assembly in the battery case and injecting an electrolyte so that the mass of the electrolyte per unit capacity is a (g / Ah), thereby assembling a battery cell; a third step of activating the battery cell; and a fourth step of pre-charging / pre-discharging the activated battery cell b times, wherein the following formula 1 is satisfied.
[0009] Formula 1: 15≤486.77-373.09×e (-0.006b) ×a 0.29≤30,
[0010] In Formula 1 above, a is an integer of 2.0 to 3.0, preferably, an integer of 2.0 to 2.5, and b is an integer of 0 to 3.
[0011] Preferably, the method for manufacturing a lithium secondary battery may satisfy the following formula 1-1.
[0012] Formula 1-1: 15≤486.77-373.09×e (-0.006b) ×a 0.29 ≤27,
[0013] In the above formula 1-1, a and b are the same as in formula 1.
[0014] Meanwhile, in the fourth step, pre-charge / pre-discharge may be performed within the SOC range of 0 to 99 at a C rate of 0.1C to 1C.
[0015] Preferably, pre-charging / pre-discharging may be performed within a voltage range of 2.50V to 4.35V.
[0016] Meanwhile, the third step of activating the battery cells may include charging / discharging the battery cells.
[0017] Meanwhile, in the present disclosure, the battery case may be a soft pack including a barrier layer, a base layer formed on one side of the barrier layer, and a sealant layer formed on the other side of the barrier layer, and the soft pack includes at least one cup portion recessed in one direction.
[0018] In addition, the ratio of the overall length to the overall width of the electrode assembly may be 5 to 10, for example, the electrode assembly may have an overall length of 400 mm to 600 mm and an overall width of 50 mm to 150 mm.
[0019] The friction force between the inner surface of the battery case and the electrode assembly of the lithium secondary battery of the present disclosure manufactured by the above method may be greater than 15 kgf, preferably, 15 kgf to 30 kgf.
[0020] In addition, the lithium secondary battery of the present disclosure manufactured by the above method showed no electrolyte leakage when subjected to a collision impact test under the collision impact condition of 133.7G×15.8ms, that is, the electrolyte leakage was zero.
[0021] In addition, the rated capacity of the lithium secondary battery may be 50 Ah to 200 Ah.
[0022] Beneficial Effects
[0023] As disclosed in the present invention, when the battery is manufactured so that the electrolyte injection amount and the pre-charge / pre-discharge times satisfy a specific relationship, the friction between the electrode assembly and the inner surface of the battery case is significantly increased compared to the prior art, thereby suppressing the separation of the electrode assembly and / or electrolyte leakage caused by external impact, thereby significantly improving the impact resistance of the lithium secondary battery.
[0024] The lithium secondary battery of the present disclosure manufactured according to the above method has a high friction of more than 15 kgf between the electrode group and the battery case. Therefore, when the collision impact test is performed under the collision condition of 133.7 G×15.8 ms, no electrolyte leakage due to damage to the battery case occurs. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a flowchart illustrating a method for manufacturing a lithium secondary battery according to the present disclosure.
[0026] Figure 2 is an exploded perspective view of a secondary battery according to an embodiment of the present disclosure.
[0027] Figure 3 is a cross-sectional view showing a soft pack according to an embodiment of the present disclosure.
[0028] Figure 4 is a graph showing the friction force measurement results of the secondary batteries manufactured according to the methods of Examples 1 to 4.
[0029] Figure 5 is a graph showing the friction force measurement results of secondary batteries manufactured according to the methods of Comparative Examples 1 and 2 and Examples 5 and 6. DETAILED DESCRIPTION
[0030] It should be understood that the words or terms used in this document and the claims of the present disclosure should not be interpreted as being limited to the meanings defined in commonly used dictionaries. It should also be understood that the words or terms should be interpreted as having the meanings consistent with their meanings in the prior art and the technical concept of the present disclosure based on the inventor's ability to appropriately define the meanings of the words or terms so that the present disclosure can be best interpreted.
[0031] Hereinafter, the present disclosure will be described in detail with reference to specific embodiments.
[0032] Nowadays, with the increasing demand for batteries that require high capacity (e.g., batteries for electric vehicles), the rated capacity of secondary battery cells continues to rise, and the weight of the electrode assembly also increases accordingly. However, as the weight of the electrode assembly increases, the phenomenon that external impact causes the electrode assembly to move and damage the battery case or break through the battery case becomes increasingly serious. When soft pack damage occurs, electrolyte leakage or electrode assembly deformation may occur, resulting in serious defects in battery performance and safety.
[0033] In order to solve the above limitations, after repeated research by the inventors, it was found that the amount of electrolyte injection (a) and the number of pre-charge / pre-discharge times (b) are closely related to the friction between the battery housing and the electrode assembly. Specifically, the inventors found that when the above a and b satisfy a specific relationship, the friction between the electrode assembly and the battery housing is significantly increased compared with the prior art, so that the damage to the battery housing caused by the separation of the electrode assembly caused by external impact is suppressed to achieve excellent impact resistance, thereby completing the present disclosure.
[0034] Specifically, the manufacturing method of the lithium secondary battery according to the present disclosure includes: a first step of preparing a battery case; a second step of placing an electrode assembly in the battery case and injecting an electrolyte so that the mass of the electrolyte per unit capacity is a (g / Ah), thereby assembling a battery cell; a third step of activating the battery cell; and a fourth step of pre-charging / pre-discharging the activated battery cell b times. In this case, the above a and b satisfy Formula 1, preferably, the following Formula 1-1.
[0035] Formula 1: 15≤486.77-373.09×e (-0.006b) ×a 0.29 ≤30,
[0036] Formula 1-1: 15≤486.77-373.09×e (-0.006b) ×a 0.29 ≤27,
[0037] In the above Formula 1 or Formula 1-1, a is an integer of 2.0 to 3.0, and b is an integer of 0 to 3.
[0038] When manufacturing the battery, when the electrolyte injection amount a per unit capacity and the pre-charge / pre-discharge times b satisfy the relationship of Formula 1 or Formula 1-1 above, the friction between the battery case and the electrode assembly is greatly increased to more than 15 kgf, thereby greatly improving the impact resistance.
[0039] Figure 1 A method for manufacturing a lithium secondary battery according to the present disclosure is shown. Figure 2 A perspective view showing a secondary battery according to an embodiment of the present disclosure, Figure 3 A cross-sectional view of a battery case (soft pack) is shown. Figures 1 to 3 The present disclosure is described in more detail.
[0040] <Method for producing lithium secondary battery>
[0041] First, a method of manufacturing a lithium secondary battery according to the present disclosure will be described.
[0042] Step 1: Prepare the battery case
[0043] First, a battery case containing an electrode assembly and an electrolyte is prepared (S1). In this case, preferably, the battery case may be a soft pack battery case, but is not limited thereto, and may be a square battery case or a cylindrical battery case.
[0044] Reference Figure 2 and Figure 3 The battery case may be a soft pack 100 including a barrier layer 20, a base layer 10 formed on one side of the barrier layer, a sealant layer 30 formed on the other side of the barrier layer, and at least one cup portion 110 recessed in one direction.
[0045] Specifically, the soft package 100 is flexible and can be manufactured in the following manner: a soft package film stack having a base layer 10, a barrier layer 20 and a sealant layer 30 stacked in sequence is inserted into a compression molding device, and a punch is used to apply pressure to a portion of the soft package film stack for stretching to form a cup portion concave in one direction.
[0046] The base layer 10 is disposed at the outermost layer of the soft package to protect the electrode assembly from external impact and to electrically insulate the electrode assembly.
[0047] The base layer 10 may be formed of at least one polymer material selected from the group consisting of, for example, polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymer, polyacrylonitrile, polyimide, polyamide, cellulose, aromatic polyamide, nylon, polyester, poly(p-phenylene benzobisoxazole), polyarylate, and Teflon.
[0048] The base layer 10 may have a single-layer structure or a multi-layer structure in which different polymer films 12 and 14 are stacked, such as Figure 3 When the base layer 10 has a multi-layer structure, an adhesive layer 16a may be interposed between polymer films.
[0049] At the same time, the total thickness of the base layer 10 can be 10 μm to 60 μm, preferably 20 μm to 50 μm, and more preferably 30 μm to 50 μm. When the base layer has a multilayer structure, the thickness is the thickness including the adhesive layer. When the base layer 10 meets the above range, durability, insulation and moldability show excellent performance. When the base layer is too thin, the durability is reduced and the base layer may be damaged during the molding process, and when the base layer is too thick, the moldability may be reduced, the overall thickness of the soft pack increases, and the battery accommodation space is reduced, resulting in a decrease in energy density.
[0050] According to an embodiment, the base layer 10 may have a laminated structure of a polyethylene terephthalate (PET) film and a nylon film. In this case, preferably, the nylon film is disposed on one side of the barrier layer 20, ie, the inner side, and the polyethylene terephthalate film is disposed on the surface side of the soft bag.
[0051] Polyethylene terephthalate (PET) has excellent durability and electrical insulation, and therefore, when the PET film is disposed on the surface side, excellent durability and insulation are exhibited. However, the adhesion between the PET film and the aluminum alloy film constituting the barrier layer 20 is weak, and the tensile performance is different, and therefore, when the PET film is disposed on the barrier layer side, separation of the base layer from the barrier layer may occur during the molding process, and the barrier layer may not be uniformly stretched, which may lead to a decrease in moldability. In contrast, the nylon film has a tensile performance similar to that of the aluminum alloy film constituting the barrier layer 20, and therefore, when the nylon film is disposed between the polyethylene terephthalate and the barrier layer, moldability can be improved.
[0052] The thickness of the polyethylene terephthalate film may be 5 μm to 20 μm, preferably 5 μm to 15 μm, more preferably 7 μm to 15 μm, and the thickness of the nylon film may be 10 μm to 40 μm, preferably 10 μm to 35 μm, more preferably 15 μm to 25 μm. When the thickness of the polyethylene terephthalate film and the thickness of the nylon film meet the above ranges, excellent moldability and rigidity after molding are exhibited.
[0053] The barrier layer 20 is used to ensure the mechanical strength of the soft pack 100, block gas or moisture from entering the secondary battery, and prevent electrolyte leakage.
[0054] The thickness of the barrier layer 20 may be 40 μm to 100 μm, more preferably 50 μm to 80 μm, and more preferably 60 μm to 801 μm. When the thickness of the barrier layer satisfies the above range, moldability is improved to increase the molding depth of the cup portion, or even when two cups are molded, cracks and / or pinholes are less likely to occur, thereby improving resistance to external stress after molding.
[0055] Meanwhile, the barrier layer 20 may be formed of a metal material, and in detail, may be formed of an aluminum alloy thin film.
[0056] The aluminum alloy film may contain aluminum and metal elements other than aluminum, for example, at least one or at least two selected from the group consisting of iron (Fe), copper (Cu), chromium (Cr), manganese (Mn), nickel (Ni), magnesium (Mg), silicon (Si) and zinc (Zn).
[0057] Preferably, the content of iron (Fe) in the aluminum alloy film may be 1.2wt% to 1.7wt%, preferably 1.3wt% to 1.7wt%, and more preferably 1.3wt% to 1.45wt%. When the content of iron (Fe) in the aluminum alloy film satisfies the above range, even if the cup portion is formed deeper, the generation of cracks or pinholes can be minimized.
[0058] The sealant layer 30 is used to seal the soft package by thermocompression bonding, and is provided as the innermost layer of the soft package film laminate 1 .
[0059] The sealant layer 30 is the surface in contact with the electrolyte and the electrode assembly after the soft package is formed, so it needs to have insulation and corrosion resistance. It is also used to completely seal the interior and prevent substances from moving between the interior and the outside, so it needs to have high sealing properties.
[0060] The sealant layer 30 can be formed of a polymer material, for example, it can be formed of at least one selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymer, polyacrylonitrile, polyimide, polyamide, cellulose, aromatic polyamide, nylon, polyester, polyphenylene benzobisoxazole, polyarylate and Teflon, and in particular, preferably, it can include polypropylene (PP) that exhibits excellent performance in mechanical properties (for example, tensile strength, stiffness, surface hardness, wear resistance, heat resistance) and chemical properties (for example, corrosion resistance).
[0061] More specifically, the sealant layer 30 may include polypropylene, cast polypropylene (CPP), acid-modified polypropylene, polypropylene-butylene-ethylene copolymer, or a combination thereof.
[0062] The sealant layer 30 may have a single-layer structure or a multi-layer structure including two or more layers formed of different polymer materials.
[0063] The thickness of the sealant layer 30 may be 60 μm to 100 μm, preferably 60 μm to 90 μm, and more preferably 70 μm to 90 μm. When the sealant layer is too thin, the sealing durability and insulation may be reduced, and when the sealant layer is too thick, the flexibility may be reduced and the total thickness of the soft envelope laminate may increase, resulting in a decrease in the energy density to volume ratio.
[0064] Meanwhile, the soft-coat laminate can be manufactured by a soft-coat laminate manufacturing method known in the art. For example, the soft-coat laminate can be manufactured by attaching the base layer 10 to the upper surface of the barrier layer 20 by an adhesive, and forming the sealant layer 30 on the lower surface of the barrier layer 20 by coextrusion molding or an adhesive, but the present embodiment is not limited thereto.
[0065] The soft bag 100 is manufactured by inserting the soft bag film laminate into a molding device and applying pressure to a portion of the soft bag film laminate using a punch to form a cup portion. In this case, the pressure may be 0.3MPa to 1MPa, preferably 0.3MPa to 0.8MPa, and more preferably 0.4MPa to 0.6MPa. When the pressure is too low when the cup portion is molded, excessive stretching may be caused, thereby wrinkles may be generated, and when the pressure is too high, stretching may not be performed well, so the molding depth may be reduced.
[0066] Meanwhile, the moving speed of the punch may be 20 mm / min to 80 mm / min, preferably 30 mm / min to 70 mm / min, and more preferably 40 mm / min to 60 mm / min. When the pressure during molding is too small or the moving speed of the punch is too fast, wrinkles may be generated due to buckling, and when the pressure during molding is too large or the moving speed of the punch is too slow, the stress concentrated at the corner of the cup during molding increases, which may generate more small holes or cracks.
[0067] The soft pack 100 manufactured by the above method includes a lower shell 101, an upper shell 102, and a folding portion 130 connecting the lower shell and the upper shell, and the upper shell and / or the lower shell includes a cup portion 110 recessed in one direction.
[0068] Specifically, Figure 2 As shown, the soft pack 100 may have a one-cup shape in which the cup portion 110 is formed only in the lower case 101, but the embodiment is not limited thereto, and the soft pack 100 may have a two-cup shape in which the cup portion is formed in both the upper case and the lower case. In the two-cup soft pack, the electrode assembly and the electrolyte are accommodated, and then the upper case is folded so that the cup portion of the upper case and the cup portion of the lower case face each other, so that a thicker electrode assembly can be accommodated than a one-cup-shaped soft pack, and thus, it is conducive to achieving high energy density.
[0069] The cup portion 110 has a receiving space for receiving the electrode assembly 200. Meanwhile, the soft pack 100 may include a platform 120 surrounding the cup portion 110. The platform 120 refers to an unmolded portion of the soft pack film laminate, that is, the remaining area except the cup portion 110. The platform 129 is a portion that is sealed by thermal bonding in the process of receiving the electrode assembly 200 in the cup portion 110, injecting the electrolyte, and then sealing.
[0070] The cup portion 110 may include a bottom surface and a peripheral surface. The peripheral surface may connect the bottom surface and the platform 120. The peripheral surface may be provided in a plurality, more specifically, four. The bottom surface may cover one side of the electrode assembly 200, and the peripheral surface may surround the periphery of the electrode assembly 200.
[0071] Meanwhile, the folding portion 130 connects the lower case 101 and the upper case 102, and is folded after the electrode assembly 200 is accommodated in the cup portion 110 and the electrolyte is injected, so that the upper case 102 seals the cup portion 110 of the lower case 101. When the folding portion 130 is included, the lower case 101 and the upper case 102 are connected as one body, thereby reducing the side portions that need to be sealed in the subsequent sealing process, thereby improving workability.
[0072] The folding portion 130 is formed to be spaced apart from the cup portion 110, and the distance between the folding portion 130 and the cup portion 110 may be about 0.5 mm to 3 mm, preferably about 0.5 mm to 2 mm. When the folding portion 130 is formed too close to the cup portion 110, folding cannot be performed well, and when the folding portion 130 is formed too far from the cup portion 110, the total volume of the secondary battery increases, thereby reducing the volume energy density. In the case of 2 cups, the folding portion may be formed to meet the above distance of each cup portion.
[0073] Step 2: Assemble the battery cells
[0074] Next, in the case where the battery case is prepared, the electrode assembly is disposed in the battery case, and an electrolyte is injected, thereby assembling a battery cell ( S2 ).
[0075] When the battery case is a soft pack, the electrode assembly 200 may be disposed in the cup portion 110 of the soft pack and an electrolyte (not shown) may be injected to manufacture a battery cell. Specifically, the electrode assembly may be disposed in the cup portion of the soft pack, an electrolyte may be injected, and then the soft pack may be folded to contact the upper case with the lower case, and heat may be applied to seal the sealant layer to manufacture a battery cell. In this case, a separate air pocket space may be formed in the platform 120.
[0076] The electrode assembly 200 may include a plurality of electrodes and a plurality of separators alternately stacked. The plurality of electrodes are alternately stacked with the separators interposed therebetween, and the electrode assembly 200 may include a positive electrode and a negative electrode having opposite polarities.
[0077] Reference Figure 2 , the electrode assembly 200 may be provided with a plurality of electrode tabs 230 welded to each other. The plurality of electrode tabs 230 are connected to the plurality of electrodes 210 and protrude outward from the electrode assembly 200, and thus may serve as a path for electrons to move between the inside and the outside of the electrode assembly 200. The plurality of electrode tabs 230 may be provided within the soft pack 100.
[0078] The electrode tab 230 connected to the positive electrode and the electrode tab 230 connected to the negative electrode may protrude in different directions relative to the electrode assembly 200. However, the embodiment is not limited thereto, and the electrode tab 230 connected to the positive electrode and the electrode tab 230 connected to the negative electrode may protrude in the same direction and be parallel to each other.
[0079] Lead 240 supplying power to the outside of the secondary battery may be connected to the plurality of electrode tabs 230 by spot welding, etc. One end of lead 240 may be connected to the plurality of electrode tabs 230 , and the other end of lead 240 may protrude outside pouch 100 .
[0080] A portion of the lead 240 may be surrounded by an insulating portion 250. For example, the insulating portion 250 may include an insulating tape. The insulating portion 250 may be disposed between the platform 120 of the first shell 101 and the second shell 102, and under this condition, the platform 120 and the second shell 102 may be thermally fused to each other. In this case, a portion of the platform 120 and the second shell 102 may be thermally fused to the insulating portion 250. Therefore, the insulating portion 250 may prevent the electricity generated by the electrode assembly 200 from flowing to the soft pack 100 through the lead 240, and keep the soft pack 100 sealed.
[0081] Meanwhile, in the present disclosure, the ratio of the total length W1 to the total width W2 of the electrode assembly 200 may be 5 to 10, preferably 5 to 8. When the ratio of the total length to the total width satisfies the above range, the effect of obtaining high energy density in a limited space can be achieved.
[0082] For example, the electrode assembly may have an overall length of 400 mm to 600 mm and an overall width of 50 mm to 150 mm, preferably, an overall length of 500 mm to 600 mm and an overall width of 50 mm to 100 mm.
[0083] Second, the electrolyte is used to move lithium ions generated by electrochemical reactions of electrodes during charge and discharge of the secondary battery, and may contain an organic solvent and a lithium salt.
[0084] Any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as an organic solvent, an ester-based solvent (e.g., methyl acetate, ethyl acetate, butyrolactone and ε-caprolactone; an ether-based solvent such as dibutyl ether or tetrahydrofuran) can be used; a ketone-based solvent (e.g., cyclohexanone); an aromatic hydrocarbon-based solvent (e.g., benzene and fluorobenzene); a carbonate-based solvent (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC)); an alcohol-based solvent (e.g., ethanol and isopropanol); a nitrile (e.g., R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group and may contain a double-bonded aromatic ring or an ether bond)); an amide (e.g., dimethylformamide); a dioxolane (e.g., 1,3-dioxolane); or cyclopentane sulfone. Among these solvents, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate having high ionic conductivity and a high dielectric constant (e.g., ethylene carbonate or propylene carbonate) and a linear carbonate-based compound having a low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred, which can improve the charge / discharge performance of the battery.
[0085] Any compound can be used as a lithium salt without particular limitation, as long as it can provide lithium ions used in lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The concentration range of the lithium salt that can be used is 0.1M to 5.0M, preferably 0.1M to 3.0M. When the lithium salt concentration is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent performance, and lithium ions can move efficiently.
[0086] In addition to the electrolyte components, the electrolyte may include additives for improving battery life characteristics, preventing battery capacity degradation, and increasing battery discharge capacity.
[0087] At the same time, in the present disclosure, the electrolyte is injected so that the amount of electrolyte per unit capacity of the secondary battery is a (g / Ah), in which case a is 2.0 to 3.0, preferably 2.0 to 2.5, and more preferably 2.1 to 2.4. The amount of electrolyte per unit capacity represents the ratio of the amount of electrolyte injection (unit: g) to the rated capacity of the secondary battery (unit: Ah). When the amount of electrolyte per unit capacity meets the above range, excellent impact resistance can be achieved without deteriorating the electrochemical properties of the secondary battery. When the amount of electrolyte is too small, the battery performance may be reduced due to insufficient electrolyte during battery operation, and when the amount of electrolyte is too large, the effect of improving impact resistance is not obvious.
[0088] Step 3: Activation
[0089] After the battery cells are assembled, an activation process ( S3 ) is performed.
[0090] The activation process can be performed by a general activation method known in the art to activate the assembled battery cells, thereby imparting electrical properties thereto and stabilizing the electrodes and electrolytes. For example, the activation process can be performed by charging and discharging the battery cells, and if necessary, an aging process and / or a degassing process can be included.
[0091] The charge / discharge process is intended to charge and discharge the battery cell to impart electrical properties and form a solid electrolyte interface (SEI) film on the electrode surface, and the charge / discharge conditions are appropriately adjusted according to the composition of the positive electrode, negative electrode and electrolyte of the battery cell. For example, in a battery using lithium nickel cobalt manganese-based oxide as a positive electrode active material and graphite as a negative electrode active material, charge / discharge can be performed at 20°C to 60°C within a voltage range of 2.0V to 4.4V.
[0092] Meanwhile, the aging process aims to ensure that the injected electrolyte is evenly distributed inside the battery cell and well penetrates into the positive and negative electrodes, and is performed by storing the battery cell at a specified temperature and humidity for a period of time. For example, the aging process can be performed at 10°C to 70°C for 0 to 72 hours, but is not limited thereto.
[0093] Meanwhile, the execution order and number of the charge / discharge process and the aging process are not particularly limited and can be appropriately adjusted as needed. For example, the charge / discharge process and the aging process can be independently performed at least once, and the aging process can be performed before and / or after the charge / discharge process.
[0094] The degassing process is intended to remove the gas inside the battery cell. During the aging process and the charge / discharge process, gas is generated when the electrolyte reacts chemically with the electrode. When gas remains in the battery cell, it may cause degradation of the electrochemical performance, so it is necessary to discharge the gas inside the battery cell. For the degassing process, any general method used in the art can be used without limitation, and there is no particular limitation. For example, the degassing process can be performed by a method of forming a gas outlet in a portion of the soft package, discharging the gas in a decompression chamber, and sealing the gas outlet by hot melt, or by forming an air cavity in a portion of the soft package, moving the gas into the air cavity by pressurization, and then cutting the air cavity to remove the gas.
[0095] Step 4: Pre-charge / Pre-discharge
[0096] Next, the activated battery cell is pre-charged / pre-discharged b times (S4). In this case, b is an integer from 0 to 3, preferably from 1 to 3. When b=0, it means that pre-charge / pre-discharge is not performed.
[0097] According to the research of the inventors, when pre-charging / pre-discharging is performed, additional electrolyte impregnation occurs during the pre-charging / pre-discharging process to reduce the amount of electrolyte at the interface between the electrode assembly and the battery housing, so that the friction between the battery housing and the electrode assembly can be increased to provide an effect of suppressing the movement of the electrode assembly caused by external impact. However, when the amount of electrolyte injection is small or the number of pre-charging / pre-discharging times is too large, the electrochemical performance of the battery may deteriorate due to the small amount of remaining electrolyte. Therefore, it is necessary to consider the amount of electrolyte injection to perform an appropriate number of pre-charging / pre-discharging times. Specifically, the number of pre-charging / pre-discharging times b that needs to be performed satisfies the above formula 1 or formula 1-1, and preferably, it is performed less than 3 times. When the number of pre-charging / pre-discharging times is greater than 3 times. The time required to manufacture the battery increases, which reduces productivity, and the manufacturing cost also increases due to the installation of multiple charging / discharging devices. In addition, as the number of pre-charging / pre-discharging times increases, expansion occurs and the thickness of the battery increases.
[0098] Pre-charge / pre-discharge can be performed within the range of SOC of 0 to 100, preferably, within the range of SOC of 0 to 99, more preferably, within the range of SOC of 0 to 98.5, and the C rate is 0.1C to 1C, preferably, 0.1C to 0.5C. When the current rate during pre-charge / pre-discharge is too high, the degradation reaction of the battery may be accelerated and the battery performance may be reduced, and when the SOC range is too small, the battery breathing may not be sufficient, so the effect of increasing friction may not be obvious.
[0099] Meanwhile, pre-charge / pre-discharge may vary depending on the active material and electrolyte used, and may be performed within a voltage range of, for example, 2.50 V to 4.35 V. When the pre-charge / pre-discharge voltage range exceeds the above range, battery performance may be degraded due to overcharge or overdischarge.
[0100] When a lithium secondary battery is manufactured so that the electrolyte injection amount a per unit capacity and the pre-charge / pre-discharge times b satisfy the relationship of Formula 1 or Formula 1-1 above, the friction between the electrode assembly and the inner surface of the battery case in contact with it (for example, the bottom surface of the cup portion of the soft pack) is greatly increased.
[0101] Specifically, the friction force between the inner surface of the battery housing and the electrode assembly of the lithium secondary battery manufactured according to the method of the present disclosure can be 15kgf or more, preferably, 15kgf to 30kgf, and more preferably, 17kgf to 30kgf. In this case, the friction force between the electrode assembly and the battery housing is measured by the following method.
[0102] A portion of the battery case (soft pack) of the lithium secondary battery was cut open, the welding portion between the negative electrode lead and the electrode assembly was cut open, and then the positive electrode tab was connected to a universal testing machine (UTM) to measure the force applied when pulled at a speed of 100 mm / min, which was evaluated as the friction between the electrode assembly and the inner surface of the battery case.
[0103] As described above, the friction between the electrode assembly and the battery case of the secondary battery according to the present disclosure is large, so even if it is subjected to external impact, the separation of the electrode assembly is less, so the damage to the battery case is minimal, thereby having excellent impact resistance. Specifically, in the lithium secondary battery according to the present disclosure, when the collision impact test is performed under the collision condition of 133.7G×15.8ms (acceleration×duration), no electrolyte leakage occurs.
[0104] The collision impact test can be performed by mounting the battery to be tested on the fixture of the drop impact equipment, letting the battery fall freely from a certain height, and then judging whether the battery is damaged. In this case, the free fall height is set taking into account the collision condition to be tested (acceleration × duration). Specifically, the impact energy under the collision condition to be tested can be converted into potential energy, and then the height that may have the converted potential energy is calculated by taking into account the weight of the battery to be tested to set the free fall height. At the same time, the damage of the battery can be evaluated based on the presence or absence of electrolyte leakage.
[0105] Embodiments of the present disclosure
[0106] Hereinafter, the present disclosure will be described in more detail through specific examples.
[0107] Example 1
[0108] A soft pack in which nylon, polyethylene terephthalate, aluminum alloy film and polypropylene were sequentially stacked and a cup portion was molded was prepared. A stacked electrode assembly with a total length of 548 mm and a total width of 99 mm was housed in the cup portion, and then an electrolyte was injected so that the amount of electrolyte per unit capacity was 2.19 g / Ah, and then sealed to manufacture a battery cell. The battery cell was then charged / discharged in a temperature range of 10°C to 70°C and a voltage range of 2.0V to 4.25V, and then activated by performing a degassing process. No pre-charge / pre-discharge was performed.
[0109] Example 2
[0110] The activated battery cell was manufactured in the same manner as Example 1, and then subjected to a pre-charge / pre-discharge process, wherein the battery cell was charged to 4.25V at 0.33C and then discharged to 2.5V at 0.33C with an SOC ranging from 0 to 98.3.
[0111] Example 3
[0112] The activated battery cell was manufactured in the same manner as Example 1, and then subjected to two pre-charge / pre-discharge processes, wherein the battery cell was charged to 4.25V at 0.33C and then discharged to 2.5V at 0.33C with an SOC ranging from 0 to 98.3.
[0113] Example 4
[0114] The activated battery cell was manufactured in the same manner as Example 1, and then subjected to three pre-charge / pre-discharge processes, wherein the battery cell was charged to 4.25V at 0.33C and then discharged to 2.5V at 0.33C with an SOC ranging from 0 to 98.3.
[0115] Comparative Example 1
[0116] A soft pack in which nylon, polyethylene terephthalate, aluminum alloy film and polypropylene were sequentially stacked and a cup portion was molded was prepared. A stacked electrode assembly with a total length of 548 mm and a total width of 99 mm was housed in the cup portion, and then an electrolyte was injected so that the amount of electrolyte per unit capacity was 2.30 g / Ah, and then sealed to manufacture a battery cell. The battery cell was then charged / discharged in a temperature range of 10°C to 70°C and a voltage range of 2.0V to 4.25V, and then activated by performing a degassing process. No pre-charge / pre-discharge was performed.
[0117] Comparative Example 2
[0118] An activated battery cell was manufactured in the same manner as in Comparative Example 1, and then a pre-charge / pre-discharge process was performed, wherein the battery cell was charged to 4.25V at 0.33C and then discharged to 2.5V at 0.33C with an SOC ranging from 0 to 98.3.
[0119] Example 5
[0120] An activated battery cell was manufactured in the same manner as in Comparative Example 1, and then subjected to two pre-charge / pre-discharge processes, wherein the battery cell was charged to 4.25V at 0.33C and then discharged to 2.5V at 0.33C with an SOC ranging from 0 to 98.3.
[0121] Example 6
[0122] An activated battery cell was manufactured in the same manner as in Comparative Example 1, and then subjected to three pre-charge / pre-discharge processes, wherein the battery cell was charged to 4.25V at 0.33C and then discharged to 2.5V at 0.33C with an SOC ranging from 0 to 98.3.
[0123] Table 1 below shows the electrolyte injection amounts (a), the number of precharge / predischarge times (b), and values calculated by Formula 1 of Examples 1 to 6 and Comparative Examples 1 and 2.
[0124] [Table 1]
[0125]
[0126] Experimental Example 1: Friction Test
[0127] A portion of the lithium secondary battery soft pack manufactured in Examples 1 to 6 and Comparative Examples 1 and 2 was cut open, the welding portion of the negative lead and the electrode assembly was cut open, and then the positive electrode tab was connected to a universal testing machine (UTM) to measure the force applied when pulled at a speed of 100 mm / min, which was evaluated as the friction between the electrode assembly and the inner surface of the battery case (the bottom surface of the cup). For accurate measurement, two or three secondary batteries were measured for each example and comparative example. The measurement results are shown in Figure 2. Figure 4 and Figure 5 shown.
[0128] like Figure 4 and Figure 5As shown, in the lithium secondary batteries of Examples 1 to 6, the electrolyte injection amount (a) and the pre-charge / pre-discharge times (b) satisfy the condition of Formula 1, and the friction force between the electrode assembly and the bottom surface of the cup portion is observed to be greater than 15 kgf, while in the lithium secondary batteries of Comparative Examples 1 and 2, the electrolyte injection amount (a) and the pre-charge / pre-discharge times (b) do not satisfy the condition of Formula 1, and the friction force between the electrode assembly and the bottom surface of the cup portion is observed to be less than 15 kgf.
[0129] Experimental Example 2: Collision Impact Test
[0130] The soft-pack type secondary batteries manufactured in Examples 1 to 6 and Comparative Examples 1 and 2 were subjected to a collision impact test under a collision condition of 133.7 G×15.8 ms. The measurement results are shown in the following Table 2. No electrolyte leakage and no separation of the electrode assembly after the test were indicated as pass, and electrolyte leakage and / or separation of the electrode assembly were indicated as fail.
[0131] [Table 2]
[0132] Crash impact test results Example 1 pass Example 2 pass Example 3 pass Example 4 pass Comparative Example 1 fail Comparative Example 2 fail Example 5 pass Example 6 pass
[0133] As shown in Table 1 above, in the lithium secondary batteries of Examples 1 to 6, the electrolyte injection amount (a) and the pre-charge / pre-discharge times (b) satisfy the conditions of Formula 1, and the friction between the electrode assembly and the bottom surface of the cup portion is large, so the separation of the electrode assembly caused by external impact is suppressed, and the battery has excellent impact resistance. On the contrary, in the lithium secondary batteries of Comparative Examples 1 and 2, the electrolyte injection amount (a) and the pre-charge / pre-discharge times (b) do not satisfy the conditions of Formula 1, and the friction between the electrode assembly and the bottom surface of the cup portion is small, so electrolyte leakage occurs in the collision impact test.
Claims
1. A method for manufacturing a lithium secondary battery, the method comprising: The first step is to prepare a battery shell; The second step is to place the electrode assembly in the battery case and inject the electrolyte so that the mass of the electrolyte per unit capacity is a (g / Ah), thereby assembling a battery cell; The third step is to activate the battery cells; as well as The fourth step is to pre-charge / pre-discharge the activated battery cell b times. Among them, the following formula 1 is satisfied: Formula 1: 15≤486.77-373.09×e (-0.006b) ×a 0.29 ≤30, In Formula 1 above, a is an integer from 2.0 to 3.0, and b is an integer from 0 to 3.
2. The method according to claim 1, wherein: Satisfying the following formula 1-1, Formula 1-1: 15≤486.77-373.09×e (-0.006b) ×a 0.29 ≤27, In the above formula 1-1, a is an integer from 2.0 to 3.0, and b is an integer from 0 to 3.
3. The method according to claim 1, wherein: a is 2.0 g / Ah to 2.5 g / Ah.
4. The method according to claim 1, wherein: In the fourth step, pre-charge / pre-discharge is performed at a C rate of 0.1C to 1C within a SOC range of 0 to 99.
5. The method according to claim 1, wherein: In the fourth step, pre-charge / pre-discharge is performed within a voltage range of 2.50V to 4.35V.
6. The method according to claim 1, wherein: The third step includes charging / discharging the battery cells.
7. The method according to claim 1, wherein: The lithium secondary battery has a friction force of 15 kgf or more between an inner surface of the battery case and the electrode assembly.
8. The method according to claim 1, wherein: The lithium secondary battery has a friction force of 15 kgf to 30 kgf between an inner surface of the battery case and the electrode assembly.
9. The method according to claim 1, wherein: When the lithium secondary battery is subjected to a collision impact test under a collision condition of 133.7 G×15.8 ms, the amount of electrolyte leakage is 0.
10. The method according to claim 1, wherein: The battery case is a soft pack including a barrier layer, a base layer formed on one side of the barrier layer, and a sealant layer formed on the other side of the barrier layer, and the soft pack includes at least one cup portion recessed in one direction.
11. The method according to claim 1, wherein: The ratio of the total length to the total width of the electrode assembly is 5 to 10.
12. The method according to claim 11, wherein: The electrode assembly has an overall length of 400 mm to 600 mm and an overall width of 50 mm to 150 mm.
13. The method according to claim 1, wherein: The rated capacity of the lithium secondary battery is 50Ah to 200Ah.